Differential Bile Acid Detection in Refractory GERD Patient Saliva Using a Simple and Sensitive Liquid Chromatography Tandem Mass Spectrometry Approach. Issue 3 (March 2022) - Perez, Nisha; Chambert, Kimberly; Ribadeneira, Maria; Currie, Mark G.; Chen, Yan; Kessler, Marco M.
Abstract : Goals: The aim was to measure bile acids in human saliva using a sensitive ultraperformance liquid chromatography tandem mass spectrometry analysis method to distinguish quantitative differences in refractory gastroesophageal reflux disease (GERD) patients as compared with proton pump inhibitor (PPI) controlled GERD patients and healthy volunteers. Study: Human saliva samples were analyzed from 2 separate studies. The first a meal-controlled pilot, in which premeal and postmeal saliva samples were analyzed from 20 healthy subjects and 20 patients with GERD symptoms controlled by PPIs. In a subsequent exploratory study, saliva was collected from 34 patients with continuing GERD symptoms despite PPI treatment (refractory GERD), 30 healthy subjects, and 30 PPI-controlled GERD patients at ≥4 hours postmeal. Results: In the meal-controlled pilot study, both healthy subjects and patients with PPI-controlled GERD, had total saliva bile acid increase for the first hour after consumption of a meal and returned to baseline levels 4 hours later. There was no difference in bile acid levels between the 2 groups. In the exploratory study, the saliva from patients with refractory GERD had statistically significant higher levels of total bile acid concentration compared with those of healthy volunteers and patients with PPI-controlled GERD ( P =0.0181). Conclusions: Bile acids can be detected and accurately quantitated in human saliva using a sensitive ultraperformance liquid chromatography tandem mass spectrometry assay. Increases above threshold could indicate an underlying disease. This method could potentially be used to evaluate biliary reflux as an underlying pathophysiology of refractory GERD.